Elaboración de una bebida chocolatada a base de leche de choclo (Zea mays l.) de dos variedades (Amarillo y blanco) con dos estabilizantes (Carboximetilcelulosa y Carragenina) y dos endulzantes (panela y sacarosa) en los laboratorios académicos de la carrera de ingeniería agroindustrial de la Universidad Técnica de Cotopaxi en el periodo 2014 - 2015 - Heredia Catota, Víctor Manuel (2016)
The grains of tender corn or choclo can be processed to extract milk a new form of taking advantage of this vegetable elaborating a drink chocolatada with the purpose of transforming the typical form of consumption of this vegetable since at the present time it is consumed in a direct way or in preserve. It was determined in the drink chocolatada the influence of the two choclo varieties (Zea mays l.) (Yellow, Blanco), with two estabilizante (Carboximetilcelulosa, Carragenina) and the two endulzante (Panela, Sucrose) in the organoleptic, physiochemical estates and microbiológicas. Taking intoacount the research it was used 1kg of grain of yellow corn (INIAP-124 Enhanced Mishca) and 1 kg of grain of white corn (INIAP-101 Precocious Floury white) in stage of mature of 125-155 days. Based on the extraction of the milk of choclo of the two varieties it was made 8 treatments, a1b1c1, a1b1c2, a1b2c1, a1b2c2, a2b1c1, a2b1c2, a2b2c1, a2b2c2. Where a1: Yellow V., a2: V. white b1: carboximetilcelulosa, b2: carragenina, c1….